2008
DOI: 10.1111/j.1460-9568.2008.06548.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid integration of young newborn dentate gyrus granule cells in the adult hippocampal circuitry

Abstract: Newborn dentate gyrus granule cells (DGCs) are integrated into the hippocampal circuitry and contribute to the cognitive functions of learning and memory. The dendritic maturation of newborn DGCs in adult mice occurs by the first 3-4 weeks, but DGCs seem to receive a variety of neural inputs at both their dendrites and soma even shortly after their birth. However, few studies on the axonal maturation of newborn DGCs have focused on synaptic structure. Here, we investigated the potentiality of output and input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 50 publications
1
51
0
1
Order By: Relevance
“…5) lags behind the study of their dendritic maturation and, in particular, its regulation by extrinsic factors has not been investigated. In standard-housed mice, by 1-wk postmitosis there is significant axonal invasion of CA3 Faulkner et al 2008;Ide et al 2008). However, electron microscopy studies addressing when these axons generate functional synapses have generated somewhat discordant results.…”
Section: Efferent Synaptic Connectivity and Plasticitymentioning
confidence: 88%
See 2 more Smart Citations
“…5) lags behind the study of their dendritic maturation and, in particular, its regulation by extrinsic factors has not been investigated. In standard-housed mice, by 1-wk postmitosis there is significant axonal invasion of CA3 Faulkner et al 2008;Ide et al 2008). However, electron microscopy studies addressing when these axons generate functional synapses have generated somewhat discordant results.…”
Section: Efferent Synaptic Connectivity and Plasticitymentioning
confidence: 88%
“…However, electron microscopy studies addressing when these axons generate functional synapses have generated somewhat discordant results. Ide et al (2008) observed that 1-wk post-mitosis MF boutons expressed vGlut1 and on occasion formed rudimentary synapses on dendritic shafts, whereas 2-wk-old MFs formed complex synapses that differed little from mature ones. Faulkner et al (2008), however, found that 2-wk-old terminals are immature and only become relatively complex at 4 wk, with continued maturation over the next 3 mo.…”
Section: Efferent Synaptic Connectivity and Plasticitymentioning
confidence: 97%
See 1 more Smart Citation
“…The vast majority of these cells differentiate into neurons and migrate into the granule cell layer of the dentate gyrus (DG). They extend dendritic processes toward the molecular layer of the DG and mossy fiber axons toward targets in the hilus and CA3 region, eventually forming input and output synaptic connections Toni et al, 2007Toni et al, , 2008Faulkner et al, 2008;Ide et al, 2008;Tronel et al, 2010;Deshpande et al, 2013;Sun et al, 2013). Although this sequence is invariable, integration of newly generated neurons into hippocampal circuits proceeds at a slower rate during adulthood than during development (Duan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Os neurônios da ZSV tendem a migrar majoritariamente para o bulbo olfatório, integrandose aos circuitos locais que compõem a memória olfativa 9 . Já as células do DG tendem a originar neurônios granulares, que se integram a circuitos hipocampais relacionados à memória declarativa 10 . Nessas duas regiões, há um tipo especializado de astrócito em formato estrelado (positivo para GFAP e nestina), que pode ser considerado a verdadeira célula-tronco neural fisiológica.…”
unclassified